L’analyse psychologique du développement des gestes professionnels : une perspective pour la prévention des TMS ? - Jean-Luc Tomás (Perspectives Interdisciplinaires sur le Travail et la Santé)
References to gestures and the body do not seem essential in the work of the forerunners of cultural-historical psychology. Vygotsky, Leontiev and Luria helped however to develop theoretical approaches that we wish to re-examine. Building on their work — some of which refers to Russian physiologists — Anokhin et Bernstein — we propose a psychological analysis model of movement and gesture. Based on the work of female operators in an industrial laundry service and the group-based self-analysis and exchange that they carried out, we were able to distinguish movement, gesture and automatisms as three aspects of the same psychophysiological reality. We show how the psychological analysis of movement and gestures in clinical activity may contribute to the sustainable prevention of MSDs. We present three types of intervention in the workplace. We believe that analysis based on the psychological structure of movement and gesture can: i) provoke debate about the relationship between the three types; ii) develop the occupational movements and gestures of workers through multiple contextualization; and, iii) support agency in workers.